Aspectos clínicos e geoepidemiológicos da COVID-19 em profissionais de enfermagem do estado do Maranhão - SILVA, Weslei Melo da (2022)
This study aimed to analyze clinical and geo-epidemiological aspects of COVID-19 in nursing professionals in Maranhão State. An ecological study with different measures of analysis was carried out, in which new cases of COVID-19 in nursing professionals registered between April 2020 and March 2021 were included. Data were collected in September 2021 from the COVID-19 Notification System of Maranhão, linked to the Department of Health of the state. The populational data of the professionals, referring to the year 2020, were obtained from the Regional Nursing Council of Maranhão. The analysis was divided into two stages. In the first stage, using SPSS 24.0 software, descriptive statistics of the clinical-epidemiological variables under investigation and logistic regression models were used to investigate factors associated with death. The incidence, mortality, and lethality rates for the disease and the incidence trend over the period were determined using Prais-Winsten regression. After geocoding the cases, the incidence rates were spatially distributed by regional health units each month and presented on thematic maps in the second stage. Scanning analysis was used to detect clusters in space and time using the discrete Poisson model and SatScan 9.2 software. Thematic maps were built using ArcGIS 10.8 software. This proposal was approved by CEP/UFMA under opinion No. 4,544,201. A total of 432 cases in health professionals were registered, of which 2,116 were nursing professionals, with a mean age of 38.11 years (SD=9.58). Most cases occurred in nursing technicians (63.23%), females (86.48%), and systemic arterial hypertension was the main comorbidity (62.03%). There was a preponderance of cases in the age group from 31 to 40 years (40.69%) and in persons of black/brown race/skin color (48.20%). The following variables were considered risk factors for death: age >60 years, comorbidities such as systemic arterial hypertension, diabetes mellitus, and obesity. The highest incidence rate occurred among nurses (22.76/1000) in May 2020, and the incidence trend decreased over the period. The highest mortality rate was observed among nurses (0.63 deaths/1,000) and the highest lethality rate (1.42%) among technicians. Spatially, the distribution of cases was heterogeneous, with rates ranging from 0 to 21.2 cases/1,000 professionals and the highest rates recorded in the health regions of Rosário, São Luís, Viana, Codó, Bacabal, Presidente Dutra, and Balsas. The spatio-temporal scan analysis detected three statistically significant (p<0.05) clusters of high relative risk, spatio-temporal cluster 1 with RR=2.00 (95%CI: 1.35-5.10) involved the health regions of Imperatriz and Açailândia, cluster 2 with RR= 3.00 (95%CI: 2.09-7.69) involved the regions of São Luís, Pinheiro and Viana, and cluster 3 with RR= 7.10 (95%CI: 3.57-11.02) involved the regions of Presidente Dutra and Timon. Such findings constitute subsidies for managers and nursing professionals in the fight against COVID-19, leading to more effective health interventions for health professionals and vulnerable territories.